The calculation of train slipstreams using large-eddy simulation. (January 2014) - Hemida, Hassan; Baker, Chris; Gao, Guangjun
High-speed trains push air to the front, sides and over the top to form a train slipstream. The extension of the slipstream to the side, top and wake flow depends on train speed, train shape, ambient conditions and the environment in which the train operates. In this paper, the slipstream and wake flow of a 1/20th scale model of a simplified five-coach ICE2-shape train running in two different environments; in open air and when passing a platform, were obtained using large-eddy simulation (LES). The flow Reynolds number was taken to be 300, 000; based on the speed and height of the train. The effect of the platform height on the train slipstream was investigated by performing simulations on a platform of different heights: 20, 60, 90 cm. To investigate the effect of mesh resolution on the results, two different computations were performed for the case of the flow around the train running in the open air using a different number of mesh nodes; a fine mesh consisting of 18, 000, 000 nodes and a coarse mesh consisting of 12, 000, 000 nodes. The results of the coarse mesh simulation were deemed to be comparable to those from the fine mesh simulation. The LES results were also compared with full-scale data and a good agreement obtained. A number of different flow regions were observed in the train slipstream: upstream region, nose region, boundary layer region, inter-carriage gap region, tail region and wake region. Localized velocity peaks were obtained near the nose of the train and in the near wake region. Coherent structures were formed at the nose, roof and inter-carriage gaps of the train. These structures spread in the slipstream and extend a long distance behind the train in the far wake flow. The maximum slipstream turbulent intensity was found in the near wake flow. The results showed that there is a significant effect of the platform height on the slipstream velocity and nose and tail pressure pulses. However, there is only a minor effect of the platform height on the static pressure along the body of the train compared with that on the nose and tail pressure pulses. In general, the slipstream velocity in the lower region of a train running in the open air was found to be larger than that around a train passing a platform. This has been related to the effect of the underbody complexities of the train.